TENTH GRADERS’ PERCEPTIONS ON THE USE OF SOCIAL MEDIA IN LEARNING ENGLISH AT SMK N 1 PGRI MEJOBO KUDUS IN THE ACADEMIC YEAR OF 2021/2022 - Saifulloh, Singgalang Daffa's; Syafei, Muh; Nuraeningsih, Nuraeningsih (Universitas Muria Kudus, 2023)
This study aims to determine the perception of X APH students at SMK N 1 PGRI Mejobo Kudus on the use of social media in learning English. In this study, researchers used descriptive qualitative research with questionnaires and interviews. The participants in this study were 18 students of class X APH SMK N 1 PGRI Mejobo Kudus. The results show that WhatsApp, YouTube, Instagram, and TikTok are applications that are widely used by students when learning English. The results also show that social media has a positive perception for students. This is because social media applications help them improve their English language skills, so students think that social media applications are important and useful in learning English.